Catching light a solar-powered permaculture demonstration farm in Indang, Cavite - Cabanero, Louise Isa E.; Palarca, Honorio T. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
Urbanization has taken the Philippines by storm. Because of the impact of rapid industrialization, many of the younger generations have opted to look for better-paying jobs in the city. This has resulted in the deterioration of the farming profession. Nevertheless, agriculture remains as the country's economic backbone, which makes the industry's preservation a vital task. However, because of low productivity, the country is having problems with food security, and has become heavily dependent on imports. The ever-increasing energy demand can also no longer be met. Lastly, we are facing environmental problems such as that of climate change because of the destructive ways of human actvity. This study aims to be able to improve and promote agricultural sustainabilty through the application of permaculture and renewable energy into the traditional Philippine agricultural model. Keywords: agriculture, permaculture, renewable energy, solar energy, demostration farm
includes appendices.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman